Studi Kasus Putusan PT Medan 141/PID.SUS/2021/PT MDN Terhadap Pentingnya Restorative Justice Dalam Penerapan Prinsip Kasih Bagi Korban Kekerasan Dalam Rumah Tangga Keluarga Kristen - Joanne Gratia; Jonathan Fide Mulya (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Marriage is the next step in strengthening feelings of love by binding oneself in love before God. Marriage is a beautiful gift given by God to humans to continue life and offspring. However, in practice, married couples often experience quarrels and this results in criminal acts of domestic violence (KDRT) which cause damage to harmonious marital relations. Domestic violence issues can be resolved through a restorative justice mechanism based on a penal mediation forum, so that married couples can handle domestic violence issues by presenting a mediator outside of court.